2020
DOI: 10.1177/2053369120910039
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance in urinary tract infections: A re-visit after five years and experience over two sites

Abstract: Objective The aim of this study was to repeat a previous audit, performed from 2009 to 2013, for the cohort of 2018 to determine how the resistance rates in urinary pathogens in women over 18 years of age have changed. A secondary aim of the study was to use resistance data from a different UK hospital in the same year to compare differences in resistance rates across different geographic locations Study design Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Aforementioned study indicated that the susceptibility of E. coli ranged from 66% for amoxicillin to 94% for ciprofloxacin and 100% for both nitrofurantoin and fosfomycin. Another study indicated increased pattern of resistance rate to co-amoxiclav along with amoxicillin in urinary pathogens among women in a UK hospital [12].…”
Section: Discussionmentioning
confidence: 98%
“…Aforementioned study indicated that the susceptibility of E. coli ranged from 66% for amoxicillin to 94% for ciprofloxacin and 100% for both nitrofurantoin and fosfomycin. Another study indicated increased pattern of resistance rate to co-amoxiclav along with amoxicillin in urinary pathogens among women in a UK hospital [12].…”
Section: Discussionmentioning
confidence: 98%
“…Of the many possible factors responsible for these developments, the overuse and inappropriate prescribing of broad-spectrum antibiotics have been implicated. 5 Hospital inpatient prescription of antimicrobial drugs has been major concern in the last few decades. For the purchasers of healthcare services and administrators, antibiotic drugs account for a major proportion of the escalating drug budget, especially in hospitals.…”
Section: Introductionmentioning
confidence: 99%